Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1093/advances/nmab018
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: How to Develop Nutrient Profiling Models Intended for Global Use: A Manual

Abstract: Nutrient profiling (NP) models aim to assess the nutritional quality of individual foods, according to their energy content and nutrient composition. NP models, initially created to prevent obesity in high-income countries, have tended to penalize dietary energy by giving lower ratings to foods containing excessive calories, fat, sugar, and salt. Energy-driven NP models may need to be reconceptualized for use in low- and middle-income countries (LMIC) where hunger, undernutrition, and micronutrient deficiencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 47 publications
0
52
0
2
Order By: Relevance
“…The study showed that current nutrient profiling methods adopted in HIC fail to capture benefit of nutrient dense food such as fortified foods that meet the nutritional needs of people in the Global South. Guidelines for developing a Nutrient Profiling system in LMICs were [64].…”
Section: Ghana-voluntary Fortification Examplementioning
confidence: 99%
“…The study showed that current nutrient profiling methods adopted in HIC fail to capture benefit of nutrient dense food such as fortified foods that meet the nutritional needs of people in the Global South. Guidelines for developing a Nutrient Profiling system in LMICs were [64].…”
Section: Ghana-voluntary Fortification Examplementioning
confidence: 99%
“…More detailed Nutrient Rich Diet (NRD) scores are e.g. NRD9.3 ( Drewnowski, 2009 ; Fulgoni et al, 2009 ) or other scores based on a higher number of nutrients ( Drewnowski et al, 2021 ; Grigoriadis et al, 2021 ; Mertens et al, 2018 ). Such scores can be calculated if detailed food consumption data are available from food balance sheets or food surveys, in combination with food nutrition databases.…”
Section: The Food System Sustainability Compassmentioning
confidence: 99%
“…The new hybrid NRFh models need to be compared to the established ones [9,10] and also tested in relation to the foods' energy density, defined as kcal/100 g. In past studies [11,12], the preference was for those profiling algorithms that showed low correlations between nutrient density scores and energy density of foods. Those NP models that score calories, total sugar, and saturated fat tend to capture the foods' energy density as opposed to their nutrient content [13][14][15]. Second, it is important to ensure that nutrient density scores generated by NP models are not correlated too highly with food prices, also expressed per 100 kcal of food [11,16].…”
Section: Introductionmentioning
confidence: 99%
“…Second, it is important to ensure that nutrient density scores generated by NP models are not correlated too highly with food prices, also expressed per 100 kcal of food [11,16]. The principal objective is not to point to higher-cost foods but to identify those foods that are both nutrient-rich and affordable [4,14].…”
Section: Introductionmentioning
confidence: 99%